(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
The essay takes its cue from considering the supervening ascertainment of the death of the disappeared, absent or presumed dead person as an event which entails changing the structure of interests dictated by these institutions. In light of the foregoing, after having noticed that, thanks to the technological evolution in the fields of molecular biology and forensic anthropology, as compared to the past, the proof of death nowadays can occur with greater probability, the essay focuses on how the mentioned proof affects the succession process relating the missing person.